A case of well‐healed foot amputation in early China (8th–5th centuries BCE). (19th October 2021) - Zhang, Xuhui; Zhan, Xiaoya; Ding, Yan; Li, Yanfeng; Yeh, Hui‐Yuan; Chen, Liang
Abstract: This research is intended to report on a case of healed foot amputation in Central Plains, China, and to provide a differential diagnosis on the amputation. The material used is an adult skeleton, dating back to 8th–5th Centuries BCE, from Chongpingyuan site, Shaanxi, China. The methods used are macroscopic observations, microscope, and X‐ray. Macroscopic observations indicated that the individual of interest was probably a male, around 50 to 70 years old, with a stature around 168.51 cm. Nearly one third of the distal end of his left tibia and fibula was absent, and the surface was remodeled with obvious signs of healing. Meanwhile, this individual suffered from osteoarthritis, lumbosacral transitional vertebrae, and several oral pathologies. Osteoarthritis was more profoundly found on the right limbs. Yue penalty (刖刑), which is often seen on scripts and artifacts in Bronze Age China, was an explanation for this amputation, while surgery amputation or traumatic incident cannot be entirely excluded. Contemporary images and artifacts of amputees suggested the usage of crutches. The social status and possibility of punitive amputation lead to the argument that this individual was unlikely to receive positive treatments after amputation. This study supplements the current research of ancient amputation in early China and provides an opportunity to look at the penal system and medical knowledge of the Zhou Dynasty. The absence of cutting marks left a questionable point with regards to the tools used for amputations.